(untitled) (Pedagogy of Higher and Secondary Education, 2003)
її is important for receiving positive results in a vocal-choral work to know and to create pedagogical conditions of rising of the quality of the vocalchoral work in the process o f pupils’ education. Pedagogical conditions of form ing o f quality of vocal-choral work mean specially created conditions owing to which deep understanding of aesthetic content of a musical composition are carried out and its influence to the personality strengthen.